The guarantees offered to the foreign investor in the Algerian legislation - Kellou, Hichem (Journal of Human Sciences, 2022)
Foreign investment is currently one of the most important means to achieve the economic and social development of developing countries, it is also an effective tool in this transfer of scientific knowledge and technology, but a foreign investor can be exposed in the practice of his subsidence investment project, he was not considered as a sovereign who could take actions that would deprive the exceptional foreigner of his property.The system consists of legal rules and material and procedural guarantees that meet international requirements and that follow the evolution and evolution adopted by the host host state with a view to attracting capital.